ISOLATED HEMIHYPERTROPHY IN CHILD - Lorena Elena Melit; Cristina Oana Marginean; Claudia Banescu; Raluca Damian; Andreea Dinca; Claudiu Marginean (Amaltea Medical Publishing House, 2016)
Hemihypertrophy or hemihyperplasia is a rare congenital condition, whose incidence is difficult to estimate, due to the fact that asymmetry is very mild, therefore remaining undiagnosed. Hemihyperplasia can be isolated or associated to certain genetic syndromes. We present the case of a 6-months-old female infant, in whom, during the neonatal period, was raised the suspicion of a congenital hemihypertrophy. She was admitted in our clinic due to the presence of a facial asymmetry. The clinical exam revealed also, besides the hemihyperplasia of the right hemiface more obvious at the level of the forehead, a hypertrophy of the right superior and inferior limbs. The laboratory tests identified a mild anemia, increased levels of transaminases and alfa-fetoprotein. The abdominal ultrasound revealed a mild hepatomegaly and the transfontanellar one discrete ventriculomegaly and frontal atrophy. The genetic test was negative, therefore the final diagnosis was of isolated hemihypertrophy. The further re-evaluations showed a decreasing level of alfa-fetoprotein, without other additional pathological elements. The particularity of the case consists in diagnosing an isolated hemohypertrophy in a 6-month-old female infant, with negative genetic test, in whom it was observed at the moment of birth a mild facial asymmetry, with afterwards favorable evolution, with progressive decrease of the alfa-fetoprotein level and normal abdominal ultrasound.